Safety awareness using a computer-based safety training at semiconductor industry - Kamarudin, N.; Ali, M. W.; Kamsah, M. Z. (Faculty of Chemical and Natural Resource Engineering, 2008)
The computer-based safety training (CBT) system was developed for the use in a semiconductor industry. The component of the CBT includes user interface, database management system, knowledge base and inference engine. This system has two main sections which are safety theory modules and accident prevention scenarios. The application of CBT was tested at the semiconductor industry. The analysis on the developed system revealed that more than 86% of the respondents have successfully increased their safety awareness and understanding towards safety at the workplace after went through the SLK system.